Hydrogen-Terminated Diamond Surface as a Gas Sensor: A Comparative Study of Its Sensitivities - Kočí, Michal; Kromka, Alexander; Bouřa, Adam; Szabó, Ondrej; Husák, Miroslav (Sensors (Basel, Switzerland), 2021)
A nanocrystalline diamond (NCD) layer is used as an active (sensing) part of a conductivity gas sensor. The properties of the sensor with an NCD with H-termination (response and time characteristic of resistance change) are measured by the same equipment with a similar setup and compared with commercial sensors, a conductivity sensor with a metal oxide (MOX) active material (resistance change), and an infrared pyroelectric sensor (output voltage change) in this study. The deposited layer structure is characterized and analyzed by Scanning Electron Microscopy (SEM) and Raman spectroscopy. Electrical properties (resistance change for conductivity sensors and output voltage change for the IR pyroelectric sensor) are examined for two types of gases, oxidizing (NO2) and reducing (NH3). The parameters of the tested sensors are compared and critically evaluated. Subsequently, differences in the gas sensing principles of these conductivity sensors, namely H-terminated NCD and SnO2, are described.
Keywords: gas detectors; metal oxide (MOX); nanocrystalline diamond (NCD)